Efektivitas Model Problem Based Learning (PBL) Berbasis Bimbingan Belajar Pada Pembelajaran Matematika Siswa Sd Inpres Maccini Sombala - Syam, Nur Sakhra; HS, Eka Fitriani; Supardi, R; Jusamawati, Jusamawati (Educatio, 2023)
This study was conducted to determine the effectiveness of the problem-based learning (PBL) model based on tutoring in mathematics learning for students of SD Inpres Maccini Sombala, through mathematics class IV A students of SD Inpres Maccini Sombala. This research uses a quantitative approach with the type of experimental research and research design, namely pre-experimental design with class IV A consisting of 30 students by paying attention to certain criteria in its selection. The research instruments used, namely observation sheets, teacher and student activities, questionnaires and learning outcomes tests. The results showed that the implementation of the problem-based learning (PBL) model based on tutoring in mathematics learning for students of SD Inpres Maccini Sombala was well implemented. The application of problem-based learning (PBL) model based on tutoring in mathematics learning of Inpres Maccini Sombala Elementary School students is effective in terms of (a) student learning activities with a value of 3.5 (very good), (b) teacher activities with a value of 3.6 (very good), (c) learning outcomes with a value of 3.5 (very good) (d) student responses with a value of 2.8 (good). The result of hypothesis testing with paired sample t-test is 0.001 <0.05. Analysis of the level of effectiveness based on 3 indicators is at a value of 3.5 with a very effective category. So through the results of data analysis that has been done, it can be concluded that the problem-based learning (PBL) learning model based on on tutoring is effective in learning mathematics for students of SD Inpres Maccini Sombala.